Superresolution live imaging of plant cells using structured illumination microscopy - Komis, George; Mistrik, Martin; Šamajová, Olga; Ovečka, Miroslav; Bartek, Jiri; Šamaj, Jozef (Nature protocols, 2015)
Although superresolution (SR) approaches have been routinely used for fixed or living material from other organisms, the use of time-lapse structured illumination microscopy (SIM) imaging in plant cells still remains under-developed. Here we describe a validated method for time-lapse SIM that focuses on cortical microtubules of different plant cell types. By using one of the existing commercially available SIM platforms, we provide a user-friendly and easy-to-follow protocol that may be widely applied to the imaging of plant cells. This protocol includes steps describing calibration of the microscope and channel alignment, generation of an experimental point spread function (PSF), preparation of appropriate observation chambers with available plant material, image acquisition, reconstruction and validation. This protocol can be carried out within two to three working days.
Keywords: Intravital Microscopy; Arabidopsis; intravitální mikroskopie; Plant Cells; rostlinné buňky